Gaya Kepemimpinan Kepala Madrasah Dalam Pengembangan Budaya Madrasah Di MI Yaa Bunayya Blitar - Imam Thaulabi; Yasin Nur Falah (eL Bidayah: Journal of Islamic Elementary Education, 2021)
This research specifically looks at the leadership style of the principal at Islamic Elementary Education Yaa Bunayya Dandong Srengat Blitar in developing the culture of the madrasa. The research method, this study uses a descriptive qualitative approach. The location of this research is Islamic Elementary Education Yaa Bunayya Dandong Srengat Blitar. The data analysis used single case analysis, while checking the validity of the data by triangulation, peer discussion and attendance extension. The end of this study found 1) The leadership style of the head of the madrasa in the development of madrasa culture at Islamic Elementary Education Yaa Bunayya Dandong Srengat Blitar tends to be democratic by looking at the leadership style of the headmaster which is related to the behavior of the entire madrasa family and the community, building effective communication with subordinates and understanding their subordinates. by accepting the differences in the activities carried out. 2) Obstacles or obstacles to the leadership style of the head of Islamic Elementary Education Yaa Bunayya Dandong Srengat in developing madrasah culture in the form of obstacles caused by the lack of awareness of all madrasa members to implement madrasah regulations voluntarily. [Penelitian ini secara khusus melihat gaya kepemimpinan kepala madrasah di MI Yaa Bunayya Dandong Srengat Blitar dalam pengembangan budaya madrasahnya. Metode penelitian, penelitian ini menggunakan pendekatan kualitatif diskriptif. Lokasi penelitian ini di MI Yaa Bunayya Dandong Srengat Blitar. Analisis data dengan analisis kasus tungggal, sedangkan pengecekan keabsahan datanya dengan triangulasi, diskusi sejawat dan perpanjangan kehadiran. Akhir penelitian ini menemukan 1) Gaya kepemimpinan kepala madrasah dalam pengembangan budaya madrasah di MI Yaa Bunayya Dandong Srengat Blitar cenderung demokratis dengan melihat gaya kepemimpinan kepala madrasah yang berhubungan dengan perilaku seluruh keluarga besar madrasah dan masyarakat, membangun komunikasi yang efektif dengan bawahan serta memahami anak buahnya dengan menerima perbedaan-perbedaannya pada kegiatan-kegiatan yang dilaksanakan. 2) Kendala atau hambatan gaya kepemimpinan kepala MI Yaa Bunayya Dandong Srengat dalam pengembangan budaya madrasah berupa kendala yang disebabkan belum adanya kesadaran dari seluruh warga madrasah untuk menjalankan peraturan madrasah secara sukarela]